‘‘Mitigating cancer pain: What else matters?”—A qualitative study into the needs and concerns of cancer patients in Sri Lanka - N. P. Edirisinghe; P. T. R. Makuloluwa; A. A. T. D. Amarasekara; C. S. E. Goonewardena (PLoS ONE, 2025)
Objectives In Sri Lanka, cancer is a significant contributor to both morbidity and mortality rates. In 2022, 33,243 new cancer cases were reported, resulting in an age- standardized incidence rate of 106.9 per 100,000 individuals. The overall experience of cancer pain reflects patients’ needs and concerns. Therefore, a thorough understanding of the patient’s needs and concerns is crucial to implementing satisfactory pain outcomes. This study aims to explore the needs and concerns of patients with cancer pain in Sri Lanka. Methods This study employed a descriptive qualitative approach among purposively selected patients with cancer and registered at the pain management unit. Participants recruited were 18 years or older with cancer-related pain. Noncancerous pain and those with psychological disorders, and brain metastases were excluded. Twenty-one semi-structured interviews were conducted until data saturation using a semi-structured interview guide, each lasting 30–60 minutes. Data were analyzed by Graneheim and Lundman’s content analysis method. Results The study primarily involved participants aged 51–60 Sinhalese Buddhists. It highlighted two main themes: ’Changes in normal lifestyle’ and ’Needs and expectations’. The ’Changes in normal lifestyle’ theme included subthemes like ’Functional limitations’, ’Emotional reactions’, ’altered interpersonal relationships’, and ’Socio-financial problems’. The ’Needs and expectations’ theme covered desires for a ’Pain-free life’, a return to a ’Normal lifestyle’, and the ’Need for a caregiver’. The findings emphasize that the most significant issue for cancer patients is the disruption to their normal lifestyle due to various challenges, while their primary need is to live without pain. Conclusions ‘Life without pain’ is a cancer sufferer’s greatest need while ’changes in normal lifestyle’ owing to bio-psycho-social-spiritual problems is their primary concern.